Influence of probiotic supplementation on the growth performance, plasma variables, and ruminal bacterial community of growth-retarded lamb - Mao, Huiling; Ji, Wenwen; Yun, Yan; Zhang, Yanfang; Li, Zhefeng; Wang, Chong (Frontiers in Microbiology, 2023)
Introduction Growth-retarded lambs would reduce the economic incomes of sheep farming. Nutritional interventions are supposed to promote gastrointestinal health and the compensatory growth of growth-retarded lambs. This study evaluated the effects of probiotic supplementation on the growth performance, plasma characteristics and ruminal bacterial community of growth-retarded lambs. Methods Twenty-four 50-days old male Hu lambs, including 8 healthy lambs (13.2 ± 1.17 kg) and 16 growth-retarded lambs (9.46 ± 0.81 kg), were used in this study. The 8 healthy lambs were fed the basal diet and considered the positive control (GN), and the other 16 growth-retarded lambs were randomly assigned into 2 groups (basal diet without probiotic [negative control, GR] and basal diet supplementation with 1 g/kg concentrate feed probiotic [GRP]), with each group having 4 replicate pens. The feeding trial lasted for 60 days with 7 days for adaptation. Results The results showed that dietary supplementation with probiotic increased (p < 0.05) the average daily gain and dry matter intake of growth-retarded lambs. For growth-retarded lambs, supplementation with probiotic increased (p < 0.05) the activities of superoxide dismutase and glutathione peroxidase, as well as the concentrations of growth hormone and immunoglobulin G. Furthermore, the highest (p < 0.05) concentrations of interleukin-6, interferon-gamma and tumor necrosis factor alpha were observed in the GR group. The concentrations of total volatile fatty acids and acetate in growth-retarded lambs were increased by probiotic supplementation (p < 0.05). The relative abundances of Ruminococcus, Succiniclasticum and Acidaminococcus were lower (p < 0.05) in growth-retarded lambs. However, probiotic supplementation increased (p < 0.05) the relative abundances of these three genera. Discussion These results indicate that dietary supplementation with probiotic are promising strategies for improving the growth performance of growth-retarded lambs by enhancing immunity and altering the ruminal microbiota.